Human skeletal muscle HSP70 response to physical training depends on exercise intensity - Liu, Y.; Lormes, W.; Baur, C.; Opitz-Gress, A.; Altenburg, D.; Lehmann, M.; Steinacker, J. M. (International Journal of Sports Medicine, 2000)
We have previously reported that HSP70 in human skeletal muscle could be induced by training. However, whether HSP70 induction is dependent upon exercise volume or exercise intensity remains unknown. The aim of the present study was to investigate the relationship between HSP70 and training intensity in rowers. Fourteen well-trained male rowers were divided into two groups (group A, n = 6; group B, n = 8). Group A performed higher intensity exercise during 1st phase, whereas group B performed higher intensity exercise during 2nd training phase. Training volume in 2nd phase increased in both groups. Both training intensity and volume were reduced in 3rd phase. Muscle samples were taken from m. vastus lateralis by fine needle biopsy before training, at the end of the 1st, 2nd and 3rd training phases. HSP70 was quantitatively determined using SDS-PAGE with silver stain. In group A, HSP70 increased significantly from 38 +/- 12 etag before training to 59 +/- 16 etag at the end of the lst training phase (loaded total protein 2.5microg), and decreased afterwards. In group B, HSP70 increase (from 36 +/- 11 etag to 50 +/- 13 etag) in the 1st phase was significantly smaller, there was a further increase of HSP70 in the 2nd phase (60 +/- 14 etag). At the end of the training, HSP70 decreased in both groups. Thus, HSP70 response to training seems to be dependent upon exercise intensity.